Mesenchymal Stem Cell–Derived Exosomes: A Promising Biological Tool in Nanomedicine - Wei, Wumei; Ao, Qiang; Wang, Xiaohong; Cao, Yue; Liu, Yanying; Zheng, Song Guo; Tian, Xiaohong (Frontiers in Pharmacology, 2021)
As nano-scale biological vesicles, extracellular vesicles (EVs)/exosomes, in particular, exosomes derived from mesenchymal stem cells (MSC-exosomes), have been studied in the diagnosis, prevention, and treatment of many diseases. In addition, through the combination of nanotechnology and biotechnology, exosomes have emerged as innovative tools for the development of nanomedicine. This review focuses on a profound summarization of MSC-exosomes as a powerful tool in bionanomedicine. It systemically summarizes the role of MSC-exosomes as a nanocarrier, drug loading and tissue engineering, and their potential contribution in a series of diseases as well as the advantages of exosomes over stem cells and synthetic nanoparticles and potential disadvantages. The in-depth understanding of the functions and mechanisms of exosomes provides insights into the basic research and clinical transformation in the field of nanomedicine.